Agroecology and resilience of smallholder food security: a systematic review - Dagunga, G.; Ayamga, M.; Laube, W.; Ansah, I.G.K.; Kornher, L.; Kotu, B.H. (Frontiers Media, 2023)
Multiple covariate shocks such as the COVID-19 pandemic, the Russia–Ukraine conflict, and pre-existing climate shocks pose serious threats to smallholder livelihoods. The cascading effects of these multiple shocks, including rising prices of fertilizers and food imports, have rekindled interest in the call for a policy shift toward agroecology. Agroecology in this study is defined as a set of practices based on ecological principles of diversity, synergy, and nutrient cycling of agroecosystems, which are capable of enhancing the resilience of smallholder food security while providing ecosystem services. Proponents of the agroecology paradigm argue that it is more sustainable and resilience-enhancing. Yet, the nexus among agroecology, resilience, and food security is less understood in the literature. Therefore, this study aimed to review the existing literature to examine how agroecology could enhance the resilience and food security of smallholders. A systematic literature search was performed on Web of Science, Scopus, and PubMed based on three keywords, viz. agroecology, resilience, and food security. Following the 2020 preferred reporting items on systematic review and meta-analysis (PRISMA) guidelines for systematic literature review, 47 articles were retained for the final review. The results provide empirical evidence that supports the potential of agroecological practices in enhancing the resilience and food security of smallholders. This study proposes a framework that links agroecology, resilience, and food security, showing the interplay among all three dimensions of agroecology—the science, policy, and practices—relevant for successful agroecological transitioning or transformation while identifying gaps for further research.